2017
DOI: 10.18632/oncotarget.19197
|View full text |Cite
|
Sign up to set email alerts
|

The role of miRNA and lncRNA in gastric cancer

Abstract: Gastric cancer is one of the most common cancers and has the highest mortality rate worldwide. It is worthwhile to explore the mechanism of gastric cancer progression. An increasing number of studies have found that non-coding RNAs including miRNA and lncRNA play important roles in gastric cancer progression. This review summarized the role of ectopic miRNA in gastric cancer proliferation, growth, migration, invasion and apoptosis. Meantime, aberrantly expressed miRNA also received a great deal of attention as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
129
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(131 citation statements)
references
References 96 publications
2
129
0
Order By: Relevance
“…Noncoding RNAs can be grouped into lncRNAs (.200 nt in length) and small noncoding RNAs (#200 nt in length), including miRNAs. Mounting evidence has shown that deregulated miRNAs and lncRNAs function as key regulators in the initiation and progression of multiple cancers, including OC, via many different pathways (44)(45)(46). Our present study, for the first time, revealed a novel ceRNA model, in which the MALAT1/miR-211/PHF19 regulatory axis participate in the pathogenesis of OC.…”
Section: Discussionmentioning
confidence: 51%
“…Noncoding RNAs can be grouped into lncRNAs (.200 nt in length) and small noncoding RNAs (#200 nt in length), including miRNAs. Mounting evidence has shown that deregulated miRNAs and lncRNAs function as key regulators in the initiation and progression of multiple cancers, including OC, via many different pathways (44)(45)(46). Our present study, for the first time, revealed a novel ceRNA model, in which the MALAT1/miR-211/PHF19 regulatory axis participate in the pathogenesis of OC.…”
Section: Discussionmentioning
confidence: 51%
“…To overcome such problems, new technology such as miRNA, lncRNA which considered potential biomarker or to regulate GC progression at the transcript or transcript level has also been developed [54] . Although these researches are still in the preclinical stage, they have been expected as a solution for the recent problems.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of cytokeratin 19 and 20 from CTCs can detect GC with sensitivity and specificity of 87.5% and 94.7%, respectively, suggesting their use in the diagnosis of GC [71]. Recently, miRNAs are emerging as biomarkers in diagnosis and treatment of cancers in general and GC in particular [72,73]. A number of miRNAs from peripheral mononuclear cells could be used as surrogate markers to highlight GC patients.…”
Section: Diagnostic Potential Of Ctc In Gcmentioning
confidence: 99%